A Case Analysis of Particle Defects Found in 220kV GIS by Ultrasonic Partial Discharge and SF6 Gas Decomposition Products Joint Detection. Issue 1 (1st January 2023) - He, Jin; Li, Songyuan; Zhang, Chi; Cao, Meng; Chen, Rong; Zhu, Xuliang
Abstract: The particles inside GIS have become the biggest factor affecting the safe and stable operation of GIS. How to effectively and timely find the particle defects is very important to ensure the reliable operation of GIS. This article describes in detail how to find particles in GIS through ultrasonic partial discharge method and comprehensive diagnosis of SF6 gas decomposition products, and gives specific solutions, which will provide very useful experience for subsequent GIS operation and maintenance.